Characterization of the extracellular vesicles, ultrastructural morphology, and intercellular interactions of multiple clinical isolates of the brain-eating amoeba, Naegleria fowleri - Russell, A. Cassiopeia; Bush, Peter; Grigorean, Gabriela; Kyle, Dennis E. (Frontiers in Microbiology, 2023)
As global temperatures rise to unprecedented historic levels, so too do the latitudes of habitable niches for the pathogenic free-living amoeba, Naegleria fowleri. This opportunistic parasite causes a rare, but >97% fatal, neurological infection called primary amoebic meningoencephalitis. Despite its lethality, this parasite remains one of the most neglected and understudied parasitic protozoans. To better understand amoeboid intercellular communication, we elucidate the structure, proteome, and potential secretion mechanisms of amoeba-derived extracellular vesicles (EVs), which are membrane-bound communication apparatuses that relay messages and can be used as biomarkers for diagnostics in various diseases. Herein we propose that N. fowleri secretes EVs in clusters from the plasma membrane, from multivesicular bodies, and via beading of thin filaments extruding from the membrane. Uptake assays demonstrate that EVs are taken up by other amoebae and mammalian cells, and we observed a real-time increase in metabolic activity for mammalian cells exposed to EVs from amoebae. Proteomic analysis revealed >2,000 proteins within the N. fowleri-secreted EVs, providing targets for the development of diagnostics or therapeutics. Our work expands the knowledge of intracellular interactions among these amoebae and subsequently deepens the understanding of the mechanistic basis of PAM.